A New Trend in Cryptographic Information Security for Industry 5.0: A Systematic Review - Zaffar Ahmed Shaikh; Fahima Hajjej; Yeter Demir Uslu; Serhat Yuksel; Hasan Dincer; Roobaea Alroobaea; Abdullah M. Baqasah; Uma Chinta (IEEE Access)
Malicious assaults and information leakage have grown in importance in practically every area of information and communication technology (ICT) in recent years. Enterprise ledger organization, preservation, security, and protection are all greatly aided by information security (IS). To maintain their positions in the market, industries must safeguard their data and other vital assets. The main goals of this paper’s systematic review, which covers the entire process of privacy protection and security, are to introduce cryptographic IS for Industry 5.0 (the Fifth Industrial Revolution) as a comprehensive solution that provides regulatory compliance and IS policies in addition to the industrial goals. The review covers the four main areas: 1) recognizing the need for frameworks to be developed for a secure Industry 5.0 lifecycle; 2) emphasizing security guidelines, procedures, and countermeasures for Industry 5.0; 3) applying control, access, and availability in real-time; and 4) proposing a futuristic architecture for industrial information security. Furthermore, the analysis of previously published state-of-the-art techniques is presented in this paper. These techniques survive with various limitations and challenges, including intercommunication exchange, fine-grained control access, and interconnectivity-related issues, which affect the adoption of an IS in industrial programs. At the end of this systematic review, we investigated a few open research problems and mentioned those that are involved in the design of cryptographic re-encryption enabled IS for future Industry 5.0 developments.